The Synergistic Effects of Polysaccharides and Ginsenosides From American Ginseng (Panax quinquefolius L.) Ameliorating Cyclophosphamide-Induced Intestinal Immune Disorders and Gut Barrier Dysfunctions Based on Microbiome-Metabolomics Analysis - Zhou, Rongrong; He, Dan; Xie, Jing; Zhou, Qingyijun; Zeng, Hongliang; Li, Hongmei; Huang, Luqi (Frontiers in Immunology, 2021)
Cyclophosphamide (CTX), used in cancer chemotherapy, a high dose of which would cause immunosuppressive effect and intestinal mucosa damage. American ginseng (Panax quinquefolius L.) has a long history of functional food use for immunological disorder, colitis, cancer, and so on. This study aimed to illustrate the underlying mechanism of American ginseng’s immunomodulatory effect in CTX-induced mice. In this study, all groups of American ginseng (American ginseng polysaccharide [AGP], American ginseng ginsenoside [AGG], co-treated with American ginseng polysaccharide and ginsenoside [AGP_AGG]) have relieve the immune disorder by reversing the lymphocyte subsets ratio in spleen and peripheral blood, as well as stimulating CD4+T cells and IgA-secreting cells in small intestine. These three treatment groups, especially AGP_AGG co-treated group recovered the intestine morphology that up-regulated villus height (VH)/crypt depth (CD) ratio, areas of mucins expression, quantity of goblet cells, and expression of tight junction proteins (ZO-1, occludin). Importantly, the microbiome-metabolomics analysis was applied in this study to illustrate the possible immuno-modulating mechanism. The synergistic effect of polysaccharides and ginsenosides (AGP_AGG group) restored the gut microbiota composition and increased various beneficial mucosa-associated bacterial taxa Clostridiales, Bifidobacterium, and Lachnospiraceae, while decreased harmful bacteria Escherichia-Shigella and Peptococcaceae. Also, AGP_AGG group altered various fecal metabolites such as uric acid, xanthurenic acid, acylcarnitine, 9,10-DHOME, 13-HDoHE, LysoPE15:0, LysoPC 16:0, LysoPI 18:0, and so on, that associated with immunometabolism or protective effect of gut barrier. These results suggest AG, particularly co-treated of polysaccharide and ginsenoside may be used as immunostimulants targeting microbiome-metabolomics axis to prevent CTX-induced side effects in cancer patients.